2021
DOI: 10.1371/journal.pone.0255787
|View full text |Cite
|
Sign up to set email alerts
|

Role of metal complexation on the solubility and enzymatic hydrolysis of phytate

Abstract: Phytate is a dominant form of organic phosphorus (P) in the environment. Complexation and precipitation with polyvalent metal ions can stabilize phytate, thereby significantly hinder the hydrolysis by enzymes. Here, we studied the stability and hydrolyzability of environmentally relevant metal phytate complexes (Na, Ca, Mg, Cu, Zn, Al, Fe, Al/Fe, Mn, and Cd) under different pHs, presence of metal chelators, and thermal conditions. Our results show that the order of solubility of metal phytate complexes is as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…These organic substances (including LMWOA) might act as substrate for microorganisms, which produce additional phytases that effectively hydrolyze phytate in the rhizosphere of soy, as demonstrated earlier (Lambers et al 2008;Wang and Lambers 2020;Wu et al 2018). This is supported by previous studies showing that the addition of commercial fungal phytases (Hayes et al 2000;Sun et al 2021) as well as the inoculation with phytate-mineralizing bacteria (Ramesh et al 2011;Richardson et al 2000) increased P availability from phytate for soy, wheat, and several pasture species. Similarly, mycorrhizal symbionts have been found to effectively mobilize P from phytate (Wang et al 2017;Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 59%
“…These organic substances (including LMWOA) might act as substrate for microorganisms, which produce additional phytases that effectively hydrolyze phytate in the rhizosphere of soy, as demonstrated earlier (Lambers et al 2008;Wang and Lambers 2020;Wu et al 2018). This is supported by previous studies showing that the addition of commercial fungal phytases (Hayes et al 2000;Sun et al 2021) as well as the inoculation with phytate-mineralizing bacteria (Ramesh et al 2011;Richardson et al 2000) increased P availability from phytate for soy, wheat, and several pasture species. Similarly, mycorrhizal symbionts have been found to effectively mobilize P from phytate (Wang et al 2017;Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Sun et al . (2021) suggested that although there are negligible differences in the thermal stability of metal phytates, Ca phytate is said to decompose significantly more (28%) than Al, Fe, Cu, Zn, Mn, Cd, Na and Mg phytates (0.05%–1.6%) under the same thermal treatments. Clearly, further analysis is required to determine the types of phytate‐mineral complexes and their thermal stability in our tissue samples.…”
Section: Resultsmentioning
confidence: 99%
“…At all pH ranges, phytate combines with calcium to form soluble complexes (Ca 1 - or Ca 2− phytate) or insoluble precipitates such as Ca 3− phytate. Strong chelating chemicals like EDTA are insufficient to dissolve complexes of metals without first reducing the metals (like Fe) ( Sun et al, 2021 ). Phytate may undergo severe immobilization, which prevents it from being hydrolyzed by phytase, resulting in its limited availability and significant accumulation in soils.…”
Section: Factors Regulating Phytate Solubilizationmentioning
confidence: 99%
“…Aspergillus niger phytase varied in its ability to prevent metal complexes from being hydrolyzed by enzymes; however, it has been discovered that the Fe phytate complex showed the most outstanding inhibition. Strong chelating chemicals like EDTA are insufficient to dissolve complexes of metals without first reducing the metals (like Fe) ( Sun et al, 2021 ). Moreover, the interactions among phytate-mineralizing bacteria, bacteria-eating nematodes, and mycorrhizal fungi also boost plant P uptake from phytate in soils with significant P adsorption ( Ranoarisoa et al, 2020 ).…”
Section: Factors Regulating Phytate Solubilizationmentioning
confidence: 99%
See 1 more Smart Citation